PENGARUH PENDIDIKAN KESEHATAN MELALUI WHATSAPP TERHADAP PENGETAHUAN TENTANG DIET SEHAT PADA PENDERITA DIABETES MELITUS - Saharudin Nisi; Kamini; Widya Nugraha (Jurnal Nurse, 2022)
This research was carried out in the area of ​​Rawa Buaya Village which is a partner of STIK Kesosi. The population in this study were all diabetics. This study aims to determine the effect of health education through WhatsApp on knowledge about the dietary patterns of people with diabetes mellitus. This study uses an experiment with a quasi-experimental approach with a non-equivalent control group design. The population in this study were all diabetics with a sample of 38 respondents in each group using a simple random sampling technique. The results in this study indicate that between the treatment and control groups the P value of Knowledge Value is 0.002. P Value of Attitude is 0.003. P Value of Diet is 0.001 . Thus, it can be concluded that there is an effect of health education through WhatsApp on the knowledge of the diet of people with diabetes mellitus. Patients' knowledge of DM is a tool that helps patients carry out diabetes management throughout their lives. Thus, the more and better the sufferer understands about his disease, the more he understands how to change his behavior and why it is necessary. So it is recommended that related parties pay more attention to people with diabetes, in providing understanding to sufferers to increase understanding and apply appropriate eating patterns.